2015
DOI: 10.1016/j.bbrep.2015.10.010
|View full text |Cite
|
Sign up to set email alerts
|

Study of rabies virus by Differential Scanning Calorimetry

Abstract: Differential Scanning Calorimetry (DSC) has been used in the past to study the thermal unfolding of many different viruses. Here we present the first DSC analysis of rabies virus. We show that non-inactivated, purified rabies virus unfolds cooperatively in two events centered at approximately 62 and 73 °C. Beta-propiolactone (BPL) treatment does not alter significantly viral unfolding behavior, indicating that viral inactivation does not alter protein structure significantly. The first unfolding event was abse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Several published studies reported DSC analysis of a number of different viruses showing diagnostically unique thermograms that provide an additional means of their characterization, [28][29][30][31]. Unique thermograms for different viruses could be due to differences in the array of proteins that typically decorate viral coat surfaces [30].…”
Section: Discussionmentioning
confidence: 99%
“…Several published studies reported DSC analysis of a number of different viruses showing diagnostically unique thermograms that provide an additional means of their characterization, [28][29][30][31]. Unique thermograms for different viruses could be due to differences in the array of proteins that typically decorate viral coat surfaces [30].…”
Section: Discussionmentioning
confidence: 99%
“…DSC data inform on unfolding of proteins and protein domains [44], thermotropic phase transitions of lipids [45], thermal transitions of RNA and DNA molecules [46][47][48] and thermally induced disassembly of viruses-the complex associations of nucleic acids with proteins and, in some cases, lipids [49]. DSC is used in development and manufacturing of several commercial vaccines [50][51][52][53][54] and informs research and development of lipid-based delivery vectors, their equivalence and similarity [19,54,55]. In addition to multiple stability metrics, DSC provides a fingerprint of Higher Order Structure defined by a range of intra-and inter-molecular interactions in a sample.…”
Section: Binding Interactionmentioning
confidence: 99%
“…It acts mainly by damaging the DNA [6]. Previous research has found that BPL chemically modifies membrane fusion proteins and antigen proteins on the surface of Influenza viruses whereas another study showed that protein structures and foldings are not greatly affected in rabies viruses [7; 8; 9]. BPL has been previously applied on bacterial cells, but it is not known if BPL affects the bacterial surface structure.…”
Section: Introductionmentioning
confidence: 99%